The impact of inflation on growth of market index - Fenilisia Kanan; Jumnibianti Nahading (Yayasan Widyantara Nawasena Raharja, 2023)
Inflation in Indonesia tends to fluctuate and has its lowest point in April 2023. This study aims to examine the relationship between inflation and market indexes in Indonesia. The sample for this study is the market index (or IHSG) for the period from January to April 2023. This study finds that inflation has a unidirectional relationship with the movement of the market index in Indonesia. In addition, this study finds that the growth of the market index throughout the observation period is 0.012%. The results of this study indicate that there is a stable condition in the capital market as the controlled inflation rates.